Can prebiotics help tackle the childhood obesity epidemic? - Wang, Yaqin; Salonen, Anne; Jian, Ching (Frontiers in Endocrinology, 2023)
Globally, excess weight during childhood and adolescence has become a public health crisis with limited treatment options. Emerging evidence suggesting the involvement of gut microbial dysbiosis in obesity instills hope that targeting the gut microbiota could help prevent or treat obesity. In pre-clinical models and adults, prebiotic consumption has been shown to reduce adiposity partially via restoring symbiosis. However, there is a dearth of clinical research into its potential metabolic benefits in the pediatric population. Here, we provide a succinct overview of the common characteristics of the gut microbiota in childhood obesity and mechanisms of action of prebiotics conferring metabolic benefits. We then summarize available clinical trials in children with overweight or obesity investigating the effects of prebiotics on weight management. This review highlights several controversial aspects in the microbiota-dependent mechanisms by which prebiotics are thought to affect host metabolism that warrant future investigation in order to design efficacious interventions for pediatric obesity.